2010
DOI: 10.1007/s00421-010-1615-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of a single-stage submaximal treadmill walking protocol in healthy, middle-aged women

Abstract: Cardiorespiratory fitness is an independent predictor of cardiovascular events in women; however, maximal oxygen consumption (VO(2max)) protocols are not always feasible. The Evaluation of Physical Activity Measures in Middle-Aged Women Study was a 6-week study designed to evaluate six physical activity (PA) measures in women, aged 45-65 years. We investigated the Ebbeling submaximal treadmill (EbbTM) protocol's ability to reflect an active lifestyle in 66 women [median (IQR) age, 51.0 (48.0, 56.5) years]. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The same poor CRF was observed in a cohort studied by our group [10]. Compared to healthy adults of similar age, RA patients have a significantly reduced CRF [8,[11][12][13]. Unfortunately, in rheumatology clinical practice, the measurement of CRF is generally nonexistent.…”
Section: Introductionsupporting
confidence: 68%
“…The same poor CRF was observed in a cohort studied by our group [10]. Compared to healthy adults of similar age, RA patients have a significantly reduced CRF [8,[11][12][13]. Unfortunately, in rheumatology clinical practice, the measurement of CRF is generally nonexistent.…”
Section: Introductionsupporting
confidence: 68%
“…Other studies have reported a wide range of values for correlations between BMI and VO 2 max [16-18], and between waist circumference and VO 2 max [16,17,19], with differences reported between the sexes. In a Finnish cross sectional study of 807 men and 633 women (age: 18–75 years) individuals within the same BMI category with normal waist circumference were more physically active and had better cardiorespiratory fitness than did those with high waist circumference [20].…”
Section: Discussionmentioning
confidence: 99%
“…38, 39 This protocol is a low-risk test for non-athletic adults. Treadmill walking speed is determined for each participant based on their age and fitness level.…”
Section: Methodsmentioning
confidence: 99%